Autonomous Effects of Catheter Radiofrequency Pulmonary Vein Isolation Ablation Using a High-Power and Short-Duration Technique - Eugene O. Perepeka (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Catheter-based pulmonary vein ablation (PVA) is the gold standard for the treatment of symptomatic, drug-refractory atrial fibrillation (AF). The effect of catheter ablation on the autonomic nervous system, particularly the parasympathetic system–referred to as the “cardioneuroeffect” – represents an important side effect that may contribute to more stable outcomes of the procedure.Aim. To investigate the intraoperative autonomic effects of high-power, short-duration pulmonary vein isolation.Materials and Methods. For this retrospective study, 49 patients with paroxysmal and persistent forms of AF were selected, in whom long-term outcomes regarding arrhythmia recurrence could be tracked. All patients underwent catheter-based radiofrequency ablation at the State Institution “National Institute of Cardiovascular Surgery named after M. M. Amosov of the National Academy of Medical Sciences of Ukraine” between May 2022 and December 2024.Results. Over a mean observation period of 19.87 ± 7.56 months (range 8-34), recurrences occurred in 19 out of 49 patients (38 %). In patients without recurrence, there was a pronounced decrease in the R-R interval during the intervention (889.33 ± 157.48 vs. 762.92 ± 133.81 ms, p=0.003) and a significant increase in heart rate (69 ± 11.96 vs. 80.67 ± 15.53 bpm, p=0.003). In patients with recurrence, changes in the R-R interval and heart rate were not statistically significant (p=0.09 and p=0.117), indicating smaller autonomic modulation. At the end of the procedure, the R-R interval and heart rate were significantly higher and lower, respectively, in the recurrence group (874.25 ± 137.06 ms vs. 762.92 ± 133.81 ms, p=0.029; 69.75 ± 11.85 vs. 80.67 ± 15.53 bpm, p=0.022). Patients with recurrence had a higher mean degree of left atrial fibrosis according to voltage mapping (1.64 ± 1.21 vs. 0.84 ± 0.72), but this difference did not reach statistical significance (p=0.11). Absence of reconnection during the intervention was observed in 62.5 % of patients without recurrence, compared to only 30.8 % in the recurrence group. Reconnection in two veins occurred exclusively in the recurrence group (54 % of cases), which was not observed in any patient without recurrence. This difference was statistically significant (p=0.003).Conclusions. During catheter radiofrequency isolation of the pulmonary veins in patients with paroxysmal and persistent AF, a more pronounced effect of cardioneuromodulation was associated with a reduction in arrhythmia recurrences during the postoperative period.